Public Servants’ Accountability Pressure When Facing the Pandemic: The Moderating Role of Accountability Awareness - Yong Ye; Yulan Lin; Xiaojun Zhang; Yifen Liu; Ziqiang Han (SAGE Open)
Public servants have faced substantial accountability pressure during the public emergency. It was evident during the pandemic. However, the factors that influence accountability pressure remain to be examined. In this study, we attempt to demonstrate that the Robbins pressure theory provides a useful conceptual framework on how factors affect accountability pressure, and a regression method using primary survey data was applied to investigate how external pressure, the public servants’ capacity, accountability awareness, and communication between superiors and subordinates influence accountability pressure in the fact of a pandemic emergency. The findings show that external pressure had a positive impact on accountability pressure, the public servants’ capacity and communication between superiors and subordinates had a negative impact on accountability pressure, and accountability awareness played a negative moderating role in the effect of external pressure on accountability pressure. This study contributes toward the limited research base, and offers the suggestion that accountability pressure would be alleviated through optimized training and learning.